Javanese Inheritance Traditions Seen from Islamic Inheritance Law and Inheritance Law - Habib, Muhammad; Ryan, Az Zahra Nashira; Nurdiyanti, Erlinda Putri; Kusumaningtyas, Mahageng; Tahir, Erni Susanty; Erlita, Upik Ari (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The tradition of inheritance of Javanese people has a peculiarity that combines Islamic values and local customs. Allah Almighty in the Qur'an regulates and explains in detail about the division of inheritance, as in QS: An-Nisa verses 7-12, verses 33 and verse 176. Allah the Just does not neglect and does not neglect the rights of every heir with very clear and perfect rules. God determines the rights of every heir with justice and wisdom. Because wealth is a milestone enforcer of life for both individuals and community groups. This study aims to analyze the inheritance tradition of Javanese society in the perspective of Islamic Inheritance Law and Customary Inheritance Law. The Javanese tradition of inheritance has several main principles, namely: a) Equality: All children are entitled to receive inheritance, both male and female, b) Wisdom: Heirs can give more inheritance to certain children based on certain considerations, such as needs, achievements, or filial piety, c) Deliberation: The distribution of inheritance is carried out by consensus between heirs. The Javanese tradition of inheritance is basically in line with Islamic Inheritance Law, although there are some differences in the technicalities of inheritance distribution. This research uses normative research methods by conducting a positive legal approach to laws and regulations and case studies using qualitative data types. The data sources used are secondary data obtained from sources in the form of official documents, books, journals, the internet and other sources related to this research. This study recommends that socialization and education be carried out to the Javanese people about Islamic Inheritance Law and Customary Inheritance Law to avoid disputes in inheritance.